Mangrove Riau: sebaran dan status perubahan - Yossi Oktorini; Eko Prianto; Vini Volcherina Darlis; Rahmatdillah Rahmatdillah; Miswadi Miswadi; Romie Jhonnerie (Dinamika Lingkungan Indonesia, 2022)
The need for data and information is an essential issue in sustainable mangrove management. The availability of data from authorized institutions is essential considering the reliability and consistency of the data, both to process techniques and data availability. This study used national mangrove and landcover data produced by the Ministry of Environment and Forestry through online services. 11 data series (2000 – 2019) obtained through the Representational State Transfer (REST) Application Programming Interface (API) service. Application of spatial analysis of vector data through geoprocessing tools and attribute data management to determine the distribution and changes in mangrove cover and the factors that trigger changes. Estimated data indicate a 13.4% decline in mangroves in Riau Province, with an average decline of 2,495.9 hectares/year. Over 98% of mangrove changes into other functions are caused by human behavior towards mangroves; we need a genuine attitude to preserve the mangroves of Riau Province for the future